2016
DOI: 10.4251/wjgo.v8.i5.474
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated radiation therapy with simultaneous integrated boost based dose escalation on neoadjuvant chemoradiation therapy for locally advanced distal esophageal adenocarcinoma

Abstract: AIM:To evaluate impact of radiation therapy dose escalation through intensity modulated radiation therapy with simultaneous integrated boost (IMRT-SIB). METHODS:We retrospectively reviewed the patients who underwent four-dimensional-based IMRT-SIBbased neoadjuvant chemoradiation protocol. During the concurrent chemoradiation therapy, radiation therapy was through IMRT-SIB delivered in 28 consecutive daily fractions with total radiation doses of 56 Gy to tumor and 5040 Gy dose-painted to clinical tumor volume, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…They reported a local recurrence rate of 11% at 22 months compared with the 29% at 3 years in this study. 11 However, the patients selected in Zeng et al study all had M0 disease, whereas most (71%) presented with N0 disease in contrast to the patients presented in this trial (13% with M1 disease and 63% with N1/N2 disease), making comparison difficult. Further follow-up will determine the importance of SIB-IMRT in local control.…”
Section: Discussionmentioning
confidence: 69%
“…They reported a local recurrence rate of 11% at 22 months compared with the 29% at 3 years in this study. 11 However, the patients selected in Zeng et al study all had M0 disease, whereas most (71%) presented with N0 disease in contrast to the patients presented in this trial (13% with M1 disease and 63% with N1/N2 disease), making comparison difficult. Further follow-up will determine the importance of SIB-IMRT in local control.…”
Section: Discussionmentioning
confidence: 69%
“…Grade I generally implies imaging findings without symptoms or only mild symptoms that do not require medical intervention 11 – 13 . No study reported grade IV or grade V RP, however three studies grouped different grades of RP as “≥ grade II” or reported only an overall rate of RP 14 16 . Grade I or II RP was the highest reported grade of RP in 13 of 19 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarizes retrospective, largely single-institutional data of IMRT-based treatment for locally advanced EC [28,29,30,31]. The largest study to date from MD Anderson Cancer Center has examined 676 patients, 413 of which were treated with 3DCRT and 263 IMRT [26].…”
Section: Intensity-modulated Radiotherapymentioning
confidence: 99%